Delivereat / Muhammad Amirul Saiful Bahry - Saiful Bahry, Muhammad Amirul (2022)
DeliverEat is an online food ordering& delivery company founded in 2012 by penangites who wants to bring conveniences to hungry diners by providing the marvelous delivery service. Our mission is to enable everyone to eat and live better through technology . Rebranding is the logo or company is intended to show more progress in the food service deivery industry in Malaysia so that many people are aware of the importance of food service delivering in Malaysia.